Incidence of intensive care unit admission, outcome and post intensive care survival in patients with diffuse large B-cell lymphoma. Issue 8 (2nd August 2016) - Wohlfarth, Philipp; Carlström, Alexander; Staudinger, Thomas; Clauss, Sabine; Hermann, Alexander; Rabitsch, Werner; Bojic, Andja; Skrabs, Cathrin; Porpaczy, Edit; Schiefer, Ana-Iris; Valent, Peter; Knöbl, Paul; et al.
Abstract: Some patients with diffuse large B-cell lymphoma (DLBCL) require intensive care unit (ICU) admission prior to or during chemotherapy. We analyzed all unscheduled ICU admissions in 331 consecutive patients (18–93 years) with newly diagnosed DLBCL. Thirty-seven patients (11.2%) required ICU treatment primarily due to hemodynamic (37.8%) or respiratory failure (24.3%). Bulky disease and high IPI score were predictive of ICU admission in the early course. ICU and hospital survival was 75.7% and 70.3%, respectively. Overall survival in ICU patients with newly diagnosed DLBCL was worse compared to non-ICU-patients (40.7% vs. 72.7% at two years). However, survival of high-risk patients (IPI 3–5), continuous complete remission, and disease-free survival did not differ. Post-ICU survival was poor in patients with relapsed/refractory DLBCL (0.1–10 months). Our observations favor unrestricted ICU support in DLBCL patients undergoing first-line therapy. ICU referral of patients with refractory/relapsed disease must be evaluated in the context of the hematologic prognosis.